In-plane magnetic penetration depth in FeSe1-xSx (x = 0, 0.04, 0.09) and FeTe1-xSex (x = 0.40) single crystals. (1st February 2019) - Purohit, G.; Pattanaik, A.; Nayak, P.
ABSTRACT: The magnetization anomaly of FeSe1– x S x ( x  = 0, 0.04, 0.09) and FeTe1– x Se x ( x  = 0.40) single crystals are examined through our Modified Phenomenological Ginzburg–Landau (MPGL) theory applicable to two-band superconducting systems. The theory in the London limit calculates the values of λ ab (0) as 445.695, 372.058 and 432.957 nm of FeSe1– x S x for x  = 0, 0.04, 0.09 which are very close to the experimental values reported by Hafiez et al. [Superconducting properties of sulfur-doped iron selenide. Phys Rev B. 2015;91(16):165109–165120] and as 534 nm for FeTe1– x Se x ( x  = 0.40) single crystal, which is close to the experimental value reported by Yadav and Paulose [Upper critical field, lower critical field and critical current density of FeTe0.60 Se0.40 single crystals. New J Phys 2009;11:103046]. In addition, the variation of temperature-dependent in-plane magnetic penetration depth λ ab ( T ) with the temperature ( T ) has been presented, which agrees well as reported by Hafiez et al. [Superconducting properties of sulfur-doped iron selenide. Phys Rev B. 2015;91(16):165109–165120] and Yadav and Paulose [Upper critical field, lower critical field and critical current density of FeTe0.60 Se0.40 single crystals. New J Phys. 2009;11:103046].